2011
DOI: 10.2478/v10136-011-0004-5
|View full text |Cite
|
Sign up to set email alerts
|

The age of biomedicine: current trends in traditional subjects

Abstract: The earliest scientific journals on biomedicine began publication in the 50s and their authors addressed the application of biology to medicine. More recently, biochemistry and biomedical engineering questions have figured more prominently. This trend is discussed in a survey of the topics appearing in the Journal of Applied Biomedicine. Pharmacological and toxicological articles have been popular over the long term and the neurosciences, chronomedicine, molecular and cell biomedicine have also been very impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Biomedicine-related fields could address to this topic, investigating ethanol and bioactive components, to comprehend which constituent predominates. Interestingly, environmental medicine which explores, among the other topics, the effects of diet on pathophysiological states, will be greatly enriched by studies on wine drinking and wine bioactive phytochemicals, also considering the growing role of this beverage all over the world (Berger, 2011). Moreover, the recent findings concerning the presence of melatonin in wine would open a new field of biomedical research, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biomedicine-related fields could address to this topic, investigating ethanol and bioactive components, to comprehend which constituent predominates. Interestingly, environmental medicine which explores, among the other topics, the effects of diet on pathophysiological states, will be greatly enriched by studies on wine drinking and wine bioactive phytochemicals, also considering the growing role of this beverage all over the world (Berger, 2011). Moreover, the recent findings concerning the presence of melatonin in wine would open a new field of biomedical research, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the recent findings concerning the presence of melatonin in wine would open a new field of biomedical research, i.e. chronobiology (Berger, 2011), with the potential use of dietary melatonin in regulating circadian rhythms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our recent study suggested that visfatin may act through inflammatory reactions to play an important role in the pathogenesis of OSCC (Tsai et al, 2013). As biomedicine is an interdisciplinary area connecting human medicine in every field, it involves the study of patho-physiological processes using the methods of modern biology and being an important way to investigate human diseases, particularly from the perspective of devising new strategies for diagnosis and therapy (Berger, 2011). The aim of this study was to further substantiate a potential role for visfatin in oral cancer by studying visfatin protein expression patterns in patients with oral cancer and precancerous tissue.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that the world's population of the elderly people will reach 1.5 billion in 2050 compared to present 600 million (Prince et al, 2013). This trend of elderly population results in the growth of aging diseases such as dementia (Berger, 2011). Currently, there are about 44 million people suffering from dementia and by 2050 their number should reach 135 million (Langa, 2015).…”
Section: Introductionmentioning
confidence: 99%